Cellular targets and molecular activity mechanisms of bee venom in cancer: recent trends and developments. (2nd October 2022) - Varol, Ayşegül; Sezen, Serap; Evcimen, Dilhan; Zarepour, Atefeh; Ulus, Gönül; Zarrabi, Ali; Badr, Gamal; Daştan, Sevgi Durna; Orbayoğlu, Asya Gülistan; Selamoğlu, Zeliha; Varol, Mehmet
Abstract: Bee venom therapy is known as a traditional approach to curing many medical conditions such as arthritis, pain and rheumatism. Bee venom also provides promising potential for treating many cancers such as breast, lung, ovary, stomach, kidney, prostate, cervical, colon and esophageal cancers, osteosarcoma, leukemia, melanoma and hepatocellular carcinoma. We therefore focused not only on the molecular activity mechanisms and cellular targets of bee venom and its components, but also on modern solutions as cutting-edge nanotechnological advances to overcome existing bottlenecks, and the latest advances in the anticancer application of bee venom in clinical settings.